2005
DOI: 10.1136/oem.2004.015024
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate use of personal protective equipment among healthcare workers in public sector hospitals and primary healthcare polyclinics during the SARS outbreak in Singapore

Abstract: Background:Singapore was affected by an outbreak of severe acute respiratory syndrome (SARS) from 25 February to 31 May 2003, with 238 probable cases and 33 deaths.Aims:To study usage of personal protective equipment (PPE) among three groups of healthcare workers (HCWs: doctors, nurses, and administrative staff), to determine if the appropriate PPE were used by the different groups and to examine the factors that may determine inappropriate use.Methods:A self-administered questionnaire survey of 14 554 HCWs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 11 publications
3
60
1
2
Order By: Relevance
“…4,5 Nosocomial infections transmitted by direct-contact can be prevented by adapting standard precautions guidelines. Appropriate use of PPE is the easiest way to prevent contact from secretions and transfer of pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Nosocomial infections transmitted by direct-contact can be prevented by adapting standard precautions guidelines. Appropriate use of PPE is the easiest way to prevent contact from secretions and transfer of pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…It can be assumed that many more cases occurred during the second wave 13 . The lack of adequate personal protective equipment (PPE) utilization in prior emerging disease outbreaks such as SARS is related to increased healthcare worker illness 14–18 …”
Section: Introductionmentioning
confidence: 99%
“…Koh et al found that candid acknowledgment of the risks and timely implementation of simple protective measures could avoid panic among HCWs . Chia et al found that a variety of factors, such as job title, reported contact with SARS patients, area of work, and Impact Events Scale scores might help to determine appropriate use of personal protective equipment (PPE) by HCWs (Chia et al 2005).…”
Section: Introductionmentioning
confidence: 99%